Dysbiosis in the Human Microbiome of Cholangiocarcinoma - Rao, Benchen; Ren, Tong; Wang, Xuemei; Wang, Haiyu; Zou, Yawen; Sun, Ying; Liu, Shanshuo; Ren, Zhigang; Yu, Zujiang (Frontiers in Physiology, 2021)
Cholangiocarcinoma (CCA) is the most common malignant tumor of the biliary system with a very poor prognosis. The human microbiome which is the sum of the genetic information of human microorganisms plays an important role in regulating the digestion, absorption, immune response, and metabolism of the host. Increasing evidence indicates a close relationship between CCA and the human microbiome. Specific alterations occur in the human microbiome of patients with CCA. Therefore, in this review, we aim to summarize the latest evidence on dysbiosis in the human microbiome of CCA. Then, we generalized the effect of Helicobacter pylori on CCA. Additionally, the potential mechanism of human microbial dysbiosis promoted the progress of CCA and its precancerous disease was also explored. Furthermore, the possibility of the human microbiome as a diagnostic and therapeutic target of CCA was discussed.